Housing defects in Kuantan : a case study on buyers’ satisfaction of housing projects - Mohd Firdaus, Osmom (2017)
Malaysia is one of the developing countries and many projects are being implemented. The construction industry helps to generate the nation’s economy as well as providing benefits to construction companies. But some of the firms acted unprofessionally by involving in projects that do not meet the standard especially in housing development. There are a lot of defects to the houses purchased by house buyers especially in terms of materials and workmanship. This study is conducted to identify and study the types of housing defect occur in housing area. Besides, the purpose of the research is to study the causes of housing defect occur in building and analyze the housing defect occur at case study area. The resident satisfactions level on their housing after defect liability period also being analyzed. The study area is located at Kuantan area. The methodology adopted is through literature review and interview with the developer and house buyers. The data are collected through questionnaires that had been distributed to the parties involved in construction industry and the house buyer in case study area. Types and causes of building defect also can be identified according to survey that has been done to people that involve in construction industry. The results also show the poor workmanship is the major contributor to poor quality of construction. In order to minimize the problem, the contactor has to provide workers with necessary experience and skills. The finding of this study can be used for future references.